Investigation of explosion severity for methane/air in a closed vessel - Syafiqah Syahirah, Ayub (2017)
Methane composition made up mostly in natural gas. It has become more important these days as it is used in various sectors including industrial purposes, electric power generation and residential applications. There are many explosions occurs in industry which involves the explosion in a confined space. Therefore, the objective of this research is to investigate the severity of an explosion in a confined space. This research is focused on the effect of equivalence ratio (ER) of methane/air mixture and vessel shape toward maximum explosion pressure (Pmax) and rate of pressure rise (dP/dt). The experiment work was performed in a 20-L spherical bomb. From the results, it can be seen that the explosion in spherical vessel gives the highest maximum explosion pressure (Pmax) and the rate of pressure rise (dP/dt), thus it portrays the most severe explosion for methane/air mixture.